Development of Medical Education in Kathmandu Medical College - Pradhan, Binita; Acharya, Jenash; Ranjit, Eurek; Bista, Meera; Dixit, Sanjaya Mani; Dixit, Hemang (Journal of Kathmandu Medical College, 2018)
Background: When the Nepal Medical Council Act was enacted in 1964 it was accepted that it would be responsible for the regulation of Medical Education in Nepal. Subsequently followed the establishments of medical colleges of which Kathmandu Medical College is one. Present Status: Kathmandu Medical College started the MBBS program back in 1997 and has since then developed over the years. The development of medical education at Kathmandu Medical College ensued subsequently with the formation of Medical Education Unit Teacher Training Cell on June 2001. First batch of teacher’s training was held on February 2003 and since then the Medical Education Department has remained active. It was in the year 2014 that Medical Education Department was strengthened further and different committees and sub-committees were formed to develop the standard of medical education to new heights. Conclusion: The medical education has developed over the years as has been recorded in this paper. There are shortcomings to be corrected. For medical education to develop further, specific steps need to be carried out in future years to meet the challenges of international accreditation.